2020
DOI: 10.21203/rs.3.rs-33553/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome-based biomimetic nanoparticles targeted to inflamed joints for enhanced treatment of rheumatoid arthritis

Abstract: Background: Glucocorticoids (GCs) show powerful treatment effect on rheumatoid arthritis (RA). However, the clinical application is limited by their nonspecific distribution after systemic administration and serious adverse reactions during long-term administration. To achieve better treatment and reduce side effect, we here established a biomimetic exosome (Exo) encapsulating dexamethasone sodium phosphate (Dex) nanoparticle (Exo/Dex), whose surface was modified with folic acid (FA)-polyethylene glycol (PEG)-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Exosomes are 30–100 nm natural nanovesicles secreted by various cell types, such as tumor cells, mesenchymal stem cells, and immune cells. Exosomes are good carriers with low cytotoxicity, non-immunogenicity, and endogenous properties ( Yan et al, 2020 ). Recently, exosome-based drug delivery systems have been studied, and it is worth noting that exosomes have a natural targeting property because of the native biological functions of the original cells, which may benefit disease treatment ( Wu et al, 2020 ).…”
Section: Nanoparticle-based Drug Delivery System In Anti-inflammatorymentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are 30–100 nm natural nanovesicles secreted by various cell types, such as tumor cells, mesenchymal stem cells, and immune cells. Exosomes are good carriers with low cytotoxicity, non-immunogenicity, and endogenous properties ( Yan et al, 2020 ). Recently, exosome-based drug delivery systems have been studied, and it is worth noting that exosomes have a natural targeting property because of the native biological functions of the original cells, which may benefit disease treatment ( Wu et al, 2020 ).…”
Section: Nanoparticle-based Drug Delivery System In Anti-inflammatorymentioning
confidence: 99%
“…They selected hexyl 5-aminolevulinate hydrochloride (HAL) to obtain HAL-containing M2 exosome (HAL@M2 Exo) and found that HAL@M2 Exo had excellent inflammation-tropism capability, as both in vitro and in vivo experiments demonstrated anti-inflammatory effects in atherosclerosis. Yan et al (2020) used exosome as carrier, encapsulating dexamethasone sodium phosphate, modified the surface with folic acid (FA)-polyethylene glycol (PEG)-cholesterol (Chol), in vitro study, the FPC-Exo/Dex drug delivery system showed anti-inflammatory effect against RAW264.7 cells.…”
Section: Nanoparticle-based Drug Delivery System In Anti-inflammatorymentioning
confidence: 99%
“…To evaluate the cytotoxicity of 5-25 mg/ml blank NVs to PC12 cells, MTT analysis was performed. 30 PC12 cells were seeded in 96-well plates at a density of 1 Â 10 4 cells per well. After the cells adhered to the wall, NGF-NVs were diluted with culture medium to concentrations of 5, 10, 15, 20 and 25 mg/mL.…”
Section: Cell Viability Assay and Toxicity Assay Of Nvsmentioning
confidence: 99%
“…Currently, GCs are the most effective anti-inflammatory drugs available for SLE [ 6 ], but clinical application is limited by their nonspecific distribution after systemic administration and serious adverse reactions during long-term administration. A recent study by Yan et al provides a promising strategy using exosomes as nanocarriers to enhance the therapeutic effect of GCs against RA [ 227 ], establishing a biomimetic exosome encapsulating dexamethasone sodium phosphate nanoparticle, whose surface was modified with folic acid (FA)-PEG-cholesterol (Chol) compound.…”
Section: Exosome-based Drug Delivery In Systemic Lupus Erythematosmentioning
confidence: 99%